Transferable Ageing Provisions in Individual Health Insurance Contracts - Florian Baumann; Volker Meier; Martin Werding (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
We consider lifetime health insurance contracts in which ageing provisions are used tosmooth the premium profile. The capital stock accumulated for each individual can bedecomposed into two parts: a premium insurance and an annuitised life insurance, onlythe latter being transferable between insurers without triggering premium changesthrough risk segmentation. In a simulation based on German data, the transferable sharedeclines in age and falls with an increasing age of entry into the contract. In spite ofdifferent benefit profiles, it is almost identical for women and men.
Keywords: D91; G22; I18; 330; Health insurance; lifetime contracts; ageing provisions; premium insurance; simulations